The impact of the Central America Free Trade Agreement on the Central American textile maquila industry - Jansen, Hans G. P.; Morley, Samuel; Kessler, Gloria; Piñeiro, Valeria; Sánchez, Marco; Torero, Máximo (International Food Policy Research Institute, 2007)
While the Central America Free Trade Agreement (CAFTA) remains a hotly debated issue in all five Central American countries that are part of the treaty, most discussions are based on preconceived opinions rather than grounded in research-based results. The point of departure of the paper is that the provisions in the agreement concerning the textile maquila industry are likely to have a significant impact on household welfare, despite the already existing preferential access of textile maquila exports to the U.S. market under the rules of origin set by the Caribbean Basin Initiative (CBI) and the U.S.–Caribbean Basin Trade Partnership Act (CBTPA). What CAFTA does for maquila production in Central America is to make permanent and expand the liberalized rules of origin (granted temporarily and unilaterally by the United States and likely to be revoked in 2008) for inputs to the maquila industry. Therefore, to assess the true impact of the maquila provisions in CAFTA, we need to compare the situations without CAFTA or the CBI/CBTPA with the situation that includes CAFTA, instead of the situations before and after CAFTA. The objectives of the paper are to analyze the likely impacts of CAFTA on the apparel value chain in Central America; assess the bottlenecks and constraints to productivity growth in the apparel industry; and identify the requirements for continuing success in the value chain. In researching the paper, we made use of a variety of methodologies, including literature review, Internet sourcing, field visits, and personal interviews with key players in the sector in all five Central American CAFTA countries. We also used computable general equilibrium (CGE) models and combined these with microsimulations based on household surveys, in order to quantify the likely effect of the maquila provisions in CAFTA on economic growth, employment, and poverty. The results suggest that, depending on the country, the maquila provisions in CAFTA add between 0.01% and 1.4% to annual economic growth and between 0.005% and 1.4% per year to employment of particularly female unskilled labor. As a result and depending on the specific country, the rate of total poverty is likely to fall by between virtually zero (Costa Rica) and 0.73% (Honduras) per year relative to a situation without CAFTA’s maquila provisions. However, the model-based analyses do not take account of the fact that the quota system for textiles and clothing (the so-called Agreement on Textiles and Clothing, or ATC) expired January 1, 2005, greatly improving the access of China and other low-cost exporters to the U.S. market. Although China has so far voluntarily restricted its apparel exports to the U.S. market, in the longer term market share will increasingly go to countries with the highest comparative advantage. The qualitative analysis in the paper suggests that a survival strategy for the Central American maquila industry should consist of two main elements. First, and in order to make maximum use of the liberalized rules of origin under CAFTA, countries should increasingly move toward full-package production instead of pure assembly. Second, identification of market niches that demand higher-quality apparel produced by firms that respect socially responsible production conditions and are able to deliver fast responsiveness is a crucial means by which the Central American textile industry can develop a comparative advantage vis-à-vis Asian suppliers, needed to survive in an increasingly competitive export market.